Periodontal evaluation in patients diagnosed with inflammatory bowel disease - Laranjeira, Nuno (2015)
Inflammatory bowel disease (IBD) is a chronic condition affecting the digestive tract in different locations1. Crohn's disease (CD) and ulcerative colitis (UC) are the most common forms of IBD, both conditions are characterized by chronic inflammation at intestinal and systemic level that seems to arise in response to a variety of stimuli. The course of IBD is characterized by periods of activity and remission, and features a wide variety of manifestations, both at intestinal and extra-intestinal level, being the oral cavity one of the most affected areas. One of the oral diseases associate with IBD is periodontal disease (PD), the fact that both diseases display an aberrant immune response to the microbiota and have common pathogenic mechanisms led to various studies reporting its association.